Fabrication and characterization of electrospun ellagic acid-loaded Poly (lactic acid)-polyethylene glycol nanofibers for biomedical application - BİLĞİÇ ALKAYA, DİLEK; AYAZ SEYHAN, SERAP; GÜNDÜZ, OĞUZHAN; CESUR, SÜMEYYE (My University, 2022)
Ellagic acid (dilactone of hexahydroxydiphenic acid, 2,3,7,8-tetrahydroxy-1-benzopyran-5,4,3-cde-1-benzopyran-5,10- dione, EA) is one of the natural polyphenolic antioxidants present in numerous fruits (pomegranate, persimmon, raspberry, black raspberry, strawberry, blueberry, peach, plumes, almonds, walnuts, mango kernel), vegetables and nuts to the tune of 100–1900 mg/kg and contributes significantly to the dietary consumption as nutraceuticals or functional foods. EA demonstrates a broad array of biological roles including anti-inflammatory, anti-carcinogenic, anti-fibrosis, anti-diabetic, anti-ulcer, anti-viral, anti-microbial, anti- apoptotic, anti-mutagenic and cardio-, hepato-renal and neuroprotective together with defense against oxidative stress, lipid peroxidation and free radical damage. Because of its multitarget pharmacological properties endowed with multiple mechanisms of action, can serve as an innovative option for several applications, such as the treatment of bacterial infections and diabet. The use of natural compounds without undesired side effects, in tissue engineering applications, is highly preferred compared to chemical drugs. In recent years, many studies have been carried out to produce nanofibrous materials by electrospinning method. Electrospun nanofibers have very large surface area, controllable pore size and tunable drug release profiles. Several biocompatible polymers with excellent biocompatibility and biodegradability including poly ethylenglycol (PEG) and poly lactic acid (PLA) have been widely used for the synthesis of nanofibers using the electrospun technique. In this study, nanofibers were obtained by adding of EA at different concentration into PLA by electrospinning technique. Morphological (SEM), molecular interaction (FT-IR), thermal analysis (DSC), antioxidant activity and physical analysis were carried out after production process. The resulting structures of nanofibers are suitable for biomedical applications.
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Polylactic acid (PLA); nanofiber; ellagic acid; electrospinning